PSYCHO CORRECTIVE TECHNOLOGIES OF SHYNESS REDUCTION IN STUDENTS – FUTURE PSYCHOLOGISTS - Stepanenko, Inna (PSYCHOLOGICAL JOURNAL, 2020)
The article concerns the need for implementing the shyness reducing system for students – future psychologists as essential precondition of formation and development of future professional psychologists. The key vector of such activity is: raising teaching staff awareness and psycho-corrective work with shy students – future psychologists. Raising teaching staff awareness includes employment of different techniques: mini-lectures, seminars, conversation, discussions and psychological workshop "Shyness as teachers see it", aimed at increasing knowledge regarding shyness, its structural components and personal formations that negatively impact the formation of future professional psychologists; mastering the skills of leveling the shyness negative expression in situations of personal interaction and professional communication among students’ youth. Psycho-corrective work with shy students – future psychologists presupposes social and psychological training "Shyness manifestation reduction in future psychologists", aimed at optimization of personal formation of structural components (cognitive, emotional and behavioral) in shy students – future psychologists; cognitive-behavioral praxes of social courage aimed at mastering the skills to carry oneself in a crowd, to communicate information (verbally, non-verbally), to persuade, to attract attention, to detect danger; leader’s coping strategies development aimed at formation of effective strategies to solve complex life situations; search for the ways of emotional support; emotional endurance fostering; cinquain "Shyness emotional reenacting" – mastering the skills of emotional liberation, realization of emotional attitude toward self-shyness; master-class "Art mix" – aimed at mastering the emotional endurance skills, reflexion, tension and anxiety states reduction; the tutorial: cognitive, emotional and behavioral that presupposed explanation to shy students the constituents of shyness at cognitive (introduction and explanation of personal formations of shyness: internality, critical self-concept, inner conflict, subjective locus of control), emotional (high level of anxiety (personal, reactive), low self-concept, proneness to self-accusations) and behavioral (introversion, the subordinate-type of behavior) levels; the method of stereotypes breaking «New personal image design» aimed at realization and accepting of the new-self that do not shy.